Yuniar - Integration of Philosophy of Mathematics and Philosophy of Education in Mathematics Learning - rustama, yuniar dwi (Maliki Interdisciplinary Journal, 2025)
Mathematics not only functions as a tool for calculation but also as a means of logical and reflective thinking rooted in the values of rationality and truth. To understand this essence, the philosophy of mathematics emerges as a discipline that examines the foundations, assumptions, and methods of thinking within mathematical structures, while the philosophy of education positions learning as a valuable process that humanizes individuals. This article aims to explore the relationship and integration between the philosophy of mathematics and the philosophy of education in the context of mathematics learning. Through a literature review from various sources, it is found that the philosophy of mathematics plays a role in providing a conceptual and rational foundation for the nature of mathematical truth, while the philosophy of education provides normative direction regarding the goals and values in the learning process. The integration of the two results in a mathematical learning approach that is rational, reflective, and humanistic, where mathematics is no longer seen merely as a collection of formulas, but as a means to develop critical, systematic, and moral thinking abilities. Thus, the integration of the philosophy of mathematics and the philosophy of education is expected to strengthen the role of education as an effort to humanize individuals through the development of logic, truth, and human values in mathematics learning.